Socio-Emotional Competencies in a Secondary Teacher Training Master’s Degree in Spain - Herencia Grillo, Amalia (2023)
Secondary education moves on in a more and more complex and changing world, where students’ and teachers’ emotions play a more relevant role. In Spain, the current Official Secondary Teacher Training Master’s Degree, which enables teachers for their future working experience, created after the Ley Orgánica de Educación (LOE) approval in 2006, does not offer any specific contents about the teaching practice, social-emotional competencies or techno-pedagogical tools; at the same time, in the current learning environment, students play a more active role and teachers act as guides or facilitators for that process. This study collects 220 active secondary teachers’ responses about their specific training on these skills and the need to include them in the master’s offer, verifying the training absence and the need for inclusion. These data support the actual use of active methodologies and the theories that urge for the inclusion of social-emotional competencies in teacher’s training. They also pose some ideas on why this competency is essential when working with teenager students in order to improve their future personal and professional life.